Ethnographic Studies of Bakor Stone Monolith and Their Implication to Tourism Development - Ajoma Simon Okwoche; Emeka Emmanuel Okonkwo; Tawo Alfred Oyong (Lakhomi Journal Scientific Journal of Culture, 2021)
Monoliths in the Cross River State of Nigerian are found in a circular form, they are commonly known as Bakor or Ikom monoliths, because of the universality in conceptualisation and the configuration of the stones, they are sometimes referred to in this research as stone circles. Bakor speaking communities hold a large number of magnificent stone carvings called Bakor monoliths which exhibit a high level of artistic, qualities, and creative awareness by the ancient civilisation that creates them. The study is aimed at examining monoliths in Bakor LGA, to ascertain the socio-cultural and religious beliefs associated with these monoliths and their contributions to tourism development in Cross River State. A mixed-method of qualitative and quantitative research was employed. The result reveals that Cross River State monoliths have the potentials of attracting tourists, and are valued by host communities. However, the monoliths are under human and natural threats. The paper advocates that if Bakor monoliths are developed for cultural tourism, it will create job opportunities, improve the living standard of the host community, generate revenue, and guaranty their preservation, among others.